Lifelong learning skills : A Review of its Importance for Engineering Students - Zuraina, Ali; Anita, Abdul Rani; N, Zulkifly; Imaduddin, Abidin (Asian Scholars Network, 2019)
Lifelong learning plays an important role in addressing the issue of learning activities that are undertaken by students throughout their life. Such is due to the fact that the lifelong learning enables students to improve their knowledge, skills and competence. The current study concerns with reviewing articles pertaining to the importance of lifelong learning skills among undergraduates in engineering fields. This qualitative study employs content analysis in analysing its data in that it synthesises and analyses articles concerning the subject matter; lifelong skills thatstudents need to develop so they may be advance in their career. In analysing data for the current study, thematic coding is employed to assist the researchersin finding the relevant themes. After data is analysed, it shows that there are three (3) significant themes emerge as the results of analysing the articles. These themes are ‘Developing creativity and innovation among engineering students’, ‘Lifelong learning skills allow studentsto improve key competencies for their future undertaking’ and ‘Lifelong learning skills encourage intrapersonal communication among engineering students’. In relation to the results obtained, the study also discusses its implications.